Clinical Evaluation of Glass-Lonomer Cement and Giomer for the Management of Cervical Caries - Nahar, Nurun; Hassan, Tareq; Uddin, Mohammed Kamal (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Giomer is a unique class of restorative material has been introduced as the true hybridization of Glass Ionomer (GI) and composite resin and has the distinguishing feature of a stable surface pre-reacted glass ionomer. Glass Ionomer Cements (GIC) are also unique restorative materials with many uses in clinical practice and provide for caries-protective fluoride releasing at the margins of restorations, as well as their ability to have the fluoride within their chemical matrix recharged by outside exposure to other fluoride-containing materials. The present study aim at clinically evaluate the comparison between the glass Ionomer cement and Giomer for the management of cervical caries. Materials and methods: The study was a cross sectional comparative study which was carried out from 01 December 2018 to 31 November 2019 in the Department of Conservative Dentistry and Endodontics, Bangladesh Dental College, Dhanmondi, Dhaka. Total number of cases was 80. The patients were divided into two groups, half of the patient (Group-1) was treated with Glass Ionomer cement and half of the patient (Group-2) was treated with Giomer restoration. The post-operative sensitivity discoloration, dislodgement of filling material and secondary caries formation were recorded. All the patients were assigned and the data were analyzed statistically by SPSS version 21. p-value < 0.05 was taken as significant. Results: The study reveals 60% of the study population was within 41 to 50 years of age group (Group-1) and 62.5% were 51 to 60 years (Group-2) 45% in (Group-1) and 10% in (Group-2) had history of post filling sensitivity, 12% in (Group-1) and 5% in (Group-2) had discoloration after restoration, 2.5% had history of dislodgement of the filling in (Group-1), no history of dislodgement of the filling in (Group-2), 2.5% had history of secondary caries formation in (Group-1) and no history of Secondary caries formation in (Group-2). Conclusion: Patients were more approachable for Giomer restoration than Glass ionomer for the management of cervical caries over a period of 12 month. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 60-64